Numerical and experimental study of integrated heat pump system - Liu, Min. (2009)
Air conditioning and drying are two main sources of energy consumption in tropical countries, and in many instances both are required at the same time. An integrated system is thus proposed in this study for providing both space cooling and convective drying of materials simultaneously via evaporator and condenser coils of a refrigeration cycle respectively. It is referred to as an integrated heat pump system(IHPS).